Pengaruh Media Digital Marketing dan Online Customer Review terhadap Keputusan Pembelian di Toko Oleh2in Cilegon - Muhamad Suhaemi; Riski Alfiah; Anizir Ali Murad (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to examine the influence of digital marketing and online customer reviews on purchasing decisions at Toko Oleh2in Cilegon. The primary focus of this research is to analyze the partial effects of digital marketing on purchasing decisions, the effect of online customer reviews on purchasing decisions, and the simultaneous impact of both variables on purchasing decisions. The respondents in this study consisted of 130 people, selected using a non-probability sampling technique with purposive sampling, meaning the sample was chosen based on specific criteria relevant to the research objectives. Data collection was carried out through the distribution of questionnaires to respondents, which were then analyzed using a quantitative approach. The data were analyzed using linear regression to determine how each independent variable influences purchasing decisions. The results of the study indicate that digital marketing has a positive and significant effect on purchasing decisions. This suggests that the more effective the digital marketing strategy, the higher the likelihood of customers making a purchase. Additionally, online customer reviews also have a positive and significant impact on purchasing decisions. This finding shows that online reviews play a crucial role in helping potential buyers make informed decisions by providing clearer and more reliable information about products or services. Overall, both independent variables—digital marketing and online customer reviews—were found to have a significant impact on purchasing decisions, both partially and simultaneously. These findings provide valuable insights for Toko Oleh2in Cilegon to enhance their digital marketing efforts and facilitate customer reviews, ultimately leading to improved purchasing decisions and stronger business competitiveness.